UNIVERSAL LEARNING DESIGN (REMUNOM, 2024)
Universal Design for Learning (UDL) is a philosophy that seeks to make the school curriculum accessible to everyone, since it is through it that the different means of representing and executing content are used. To this end, this article aims to analyze how Universal Design for Learning (UDL) is used in a public education institution in the city of Linhares-ES. Using qualitative questions as a research method, the structured interview tool, containing sixteen discursive questions, was used as a field for data collection, directed to the teacher who works in specialized educational services in the multifunctional resource room of the institution in question. The expected results of this analysis aim to understand the pedagogical practices related to UDL, identifying challenges and possibilities for implementation in the school context. Thus, by investigating the application of UDL, the article aims to contribute to the debate on educational inclusion, highlighting the importance of curricular and methodological adaptations that promote accessibility and equity in education.